Your Money, Your Future : A Practical Money Management Guide for Students and Their Families - International Finance Corporation (World Bank, Washington, DC, 2014)
This guide has been created to assist potential student borrowers and their families in making decisions regarding money management. It is intended for students who are considering attending or are already enrolled in a tertiary education institution, and covers topics such as student loans, goal-setting, and repaying debt. The guide aims to educate students in order to make them better money managers and more responsible borrowers throughout their university careers and beyond. This document is divided into seven chapters: 1) basic financial issues; 2) creating and managing a budget; 3) student loans; 4) establishing credit; 5) managing debt; 6) repaying debt; and 7) saving and its benefits.